Users' preferences of usability and sustainability of old urban parks in Tabriz, Iran. - Ahmad, Hami; Maulan, Suhardi; Mariapan, Manohar; Habib, Shahhosseini (INSInet Publication, 2011)
Parks should be noble public spaces that provide greenery and nature not only for people to enjoy but also for a particular city to be sustainable with its ecological functions and values. However, some of these parks fail to attract people to visit and use them. El Goli, a park in the city of Tabriz, is an example of a park that people do not use frequently as they had before. One of the factors presumes to contribute to the problem of idle parks is that the parks fail to provide the activities people prefer. Therefore, this study is about users preferences for parks activities in the city of Tabriz, Iran. To gauge people preferences for park activities, 208 of the park were surveyed. The result shows walking and picnicking were rated as the most preferred activities and from the factor analysis of the activities items; three activities groups emerged. They are 'appreciation and exploration of nature', 'social interaction', and 'group physical activity' and 'passive involvement'. The result of analysis shows that 'appreciation and exploration of nature' group has the highest preference mean score.